Concrete Release Agent from Waste Material for Sustainable Concrete Casting - CHE DALIM, MUHAMMAD HAKEEM FIEDAUS; Andri Kusbiantoro, (Progress in Engineering Application and Technology, 2025)
Concrete is an essential material in modern construction, and its efficient casting and demoulding processes rely on the use of release agents. However, conventional release agents pose significant environmental risks. This study investigates the potential of waste-based alternatives by formulating and evaluating blends of used cooking oil (UCO) and used engine oil (UEO). The performance of these blends was assessed through infrared analysis, rebound hammer tests, and compressive strength evaluations. The findings revealed that blends consisting of 100% used engine oils, particularly when applied to steel formworks, can effectively replace conventional agents while preserving structural integrity. Based on these results, the use of 100% Used Engine Oil applied on steel formworks is recommended to enhance sustainability in the construction industry.